2021
DOI: 10.1002/cche.10478
|View full text |Cite
|
Sign up to set email alerts
|

Nitrogen fertilization levels influence the physicochemical properties of floury rice varieties

Abstract: Rice (Oryza sativa L.) is one of the three most important crops grown worldwide and is a staple food for more than 34% of the global population. Due to the changes in dietary pattern (i.e., increased consumer preference for fast food), the annual rice consumption per capita has declined 2.3% annually over the past 30 years (KOSTAT, 2019), while wheat flour consumption has increased. Therefore, food science research has begun to

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 27 publications
0
4
0
Order By: Relevance
“…According to the results, the differences in sake fermentation properties in this study are probably not related to the different proportions of cracked rice from the low‐N and high‐N treatments. To understand the mechanism underlying the different fermentation properties of sake, more in‐depth analyses of rice characteristics, such as physicochemical properties of starch (Han et al, 2021; Yang et al, 2020; Zhou et al, 2020), should be conducted.…”
Section: Resultsmentioning
confidence: 99%
“…According to the results, the differences in sake fermentation properties in this study are probably not related to the different proportions of cracked rice from the low‐N and high‐N treatments. To understand the mechanism underlying the different fermentation properties of sake, more in‐depth analyses of rice characteristics, such as physicochemical properties of starch (Han et al, 2021; Yang et al, 2020; Zhou et al, 2020), should be conducted.…”
Section: Resultsmentioning
confidence: 99%
“…The N3 and N4 treatments in the present study mainly reflect the effect of topdressing on the physical and chemical properties of starch at the jointing stage. It was found that nitrogen fertilizer application at the jointing stage significantly affected the particle size distribution of sorghum starch, but the application of nitrogen fertilizer at the jointing stage should be appropriate [ 23 ]. On the contrary, (very high) nitrogen fertilizer reduces the size of sorghum starch granules (N3 > N4).…”
Section: Discussionmentioning
confidence: 99%
“…Refer to Han et al. (2021) method with a minor modification, the pasting properties of rice flour were determined using a Rapid Visco‐Analyzer (RVA 4500, Broadcom Instruments Ltd., Patron). For the RVA procedure, 3.0 g rice flour (14% dry basis) and 25 ml of distilled water were mixed in an aluminum canister.…”
Section: Methodsmentioning
confidence: 99%
“…Refer to Han et al (2021) method with a minor modification, the pasting properties of rice flour were determined using a…”
Section: Pasting Properties Of Ricementioning
confidence: 99%